Effect of host density and location on the percentage parasitism, fertility and induced mortality of Aganaspis daci (Hymenoptera: Figitidae), a parasitoid of Ceratitis capitata (Diptera: Tephritidae) - De-Pedro, Luis; Beitia, Francisco J.; Ferrara, Fernando; Asís, Josep D.; Sabater-Munoz, Beatriz; Tormos, José (2018)
The percentage parasitism, fertility and induced mortality (mortality of host pupae attributed to parasitoids, from which adults do not emerge) of the parasitoid Aganaspis dad (Weld) infesting larvae of Ceratitis capitata (Wiedemann) were studied under laboratory and greenhouse conditions for temperature, host location (larvae provided in artificial diet or inside fruit) and host density. For larvae in artificial diet in the laboratory, our findings revealed that 23-25 C is the most suitable temperature range, leading to high rates of parasitism, fertility, induced mortality, population reduction (total mortality of C capitata caused by the parasitoid, i.e., induced mortality + percentage parasitism), and female-biased sex ratio (WM + cicS = 0.55). Regarding host density, parasitism and fertility corresponded to a Type III functional response with a female-biased sex ratio (0.54-0.61), while induced mortality decreased with an increase in host density, and population reduction presented the same type of response as parasitism and fertility. Regarding the larvae inside fruits in the laboratory, the analysis showed that parasitism and fertility, depending on host density, also showed a Type III functional response and female-biased sex ratio (0.51-0.62). For larvae provided inside fruits in the greenhouse, our results showed no significant differences regarding fruit position or host density on the percentage parasitism, induced mortality or population reduction, although there was a female-biased sex ratio (fruit position: 0.64-0.72; density: 0.66-0.76). Regarding host density, parasitism and fertility corresponded to a Type II functional response. The induced mortality decreased with increasing density and host population reduction had the same type of response as parasitism and fertility. The information reported here on the key demographic parameters and functional response of A. dad infesting C capitata under various environments and situations, will assist to evaluate the potential use of this parasitoid as a biological control agent against this pest. Our results show A. daci displays an excellent ability to locate, capture, parasitise, or simply kill C capitata, under laboratory and field conditions. (C) 2016 Elsevier Ltd. All rights reserved.